An Overview of COVID-19's Impact on English Language University Admissions and Placement Tests. Issue 1 (1st January 2021) - Ockey, Gary J.
ABSTRACT: The COVID-19 pandemic led to rapid innovation among language assessment developers who had to adapt their testing processes to address various restrictions from governments and institutions. This overview introduces some of the challenges and opportunities test developers grappled with during this period as well as introduces the six commentaries provided in the special issue. These commentaries were written by testing teams in various higher education contexts who were tasked with modifying their assessments in the rapidly evolving situation associated with the pandemic. The assessment contexts described in this special issue range from relatively small-scale local placement to international large-scale.